2019
DOI: 10.1039/c9nr01096c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-performance of self-powered flexible quantum dot photodetectors by a double hole transport layer structure

Abstract: Flexible quantum dot photodetectors with large specific detectivity, excellent weak-light responsivity, and outstanding mechanical and electrical stability were successfully fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Both rigid and flexible broadband photodetectors based on CdSeTe colloidal QDs have been made by our group [3,18]. These detectors reached remarkably high detectivity of more than 2 × 10 12 Jones in the range of 300-800 nm without an external bias voltage [18]. These results demonstrate that QDs based detectors have excellent performance.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both rigid and flexible broadband photodetectors based on CdSeTe colloidal QDs have been made by our group [3,18]. These detectors reached remarkably high detectivity of more than 2 × 10 12 Jones in the range of 300-800 nm without an external bias voltage [18]. These results demonstrate that QDs based detectors have excellent performance.…”
Section: Introductionmentioning
confidence: 93%
“…Peng et al assembled a flexible photodetector based on the PbS QDs/ZnO nanoparticles with a detectivity of 3.98 × 10 12 Jones [17]. Both rigid and flexible broadband photodetectors based on CdSeTe colloidal QDs have been made by our group [3,18]. These detectors reached remarkably high detectivity of more than 2 × 10 12 Jones in the range of 300-800 nm without an external bias voltage [18].…”
Section: Introductionmentioning
confidence: 99%
“…2a, the rise time (t rise ) or decay time (t decay ) is the duration of the transient current density increase from 10% to 90% of the maximal current density, or decrease from 90% to 10% of the maximal current density, respectively. 18,24,29,33,40,42,43 The t is closely related to the film quality, the roughness of the surface or interface and the trap states. 32,44 Hence, a smaller t indicates a more sensitive photodetector to the light signal.…”
Section: Response Time (S)mentioning
confidence: 99%
“…Besides, the displayed LDR and bandwidth also indicated that the device had imaging capabilities. 97 PbS QD-based NIR photodetectors have been obtained with fascinating properties, 98 other NIR QDs, such as PbSe, 99,100 HgTe, [101][102][103] CdSe x Te 1Àx 29,40 and toxic-free CuInSe 2…”
Section: Near-infrared (Nir) Qd-based Photodetectormentioning
confidence: 99%
“…Quantum dots (QDs) have been widely used to fabricate flexible PDs as typical 0D nanomaterials. [35][36][37][38] The band structure of QDs follows the quantum size effect. When the material size is reduced to the nanoscale, the electron energy levels near the Fermi level of the material will change from a continuous state to discrete distribution.…”
Section: Zero-dimensional (0d) Nanomaterialsmentioning
confidence: 99%